Media Moodle dalam Pembelajaran Menulis Forumsbeitrag Mahasiswa Program Studi Pendidikan Bahasa Jerman - Abdul Kasim Achmad; Nurming Saleh; Misnawaty Usman; Arlian Fachrul Syaputra (Seminar Nasional LP2M UNM, 2019)
Media of Moodle in Writing Skills in Forumsbeitrag the Students of the German Language Education Faculty of Langauge and Literature Universitas Negeri Makassar. This study aims to obtain data and information regarding the use of Moodle on the writing skills of german language Forumsbeitrag in fourth semester students of the German Language Study Program at FBS UNM. Moodle is software that is used to develop and run Internet-based learning that has features such as uploading and sharing material, forums and conversations, quizzes, gathering and reviewing assignments, and recording grades. Forumsbeitrag is writting or written in a discussion forum to discuss a theme. In the Goethe-Institut German standard B1 level exam, Forumsbeitrag is the second part of the writing test. The design of this study is quasi-experimental. The research subjects were 52 students of fourth semester who programmed the course Schriftlicher Ausdruck consisting of 27 students in class A as an experimental class and 25 people in class B as a control class. Data is collected by providing a pretest and posttest in the form of writing Forumsbeitrag. Data analysis was performed through normality test, homogeneity test and t-test. The results showed that t-count = 1.50 < t-table = 2.009 at the 0.05 significance level. This means that Moodle is not effective in learning of writing the Forumsbeitrag for students in the German Language Study Program, FBS UNM.